Simultaneous atmospheric water production and 24-hour power generation enabled by moisture-induced energy harvesting - Tingxian Li; Minqiang Wu; Jiaxing Xu; Ruxue Du; Taisen Yan; Pengfei Wang; Zhaoyuan Bai; Ruzhu Wang; Siqi Wang (Nature Communications, 2022)
Abstract Water and electricity scarcity are two global challenges, especially in arid and remote areas. Harnessing ubiquitous moisture and sunlight for water and power generation is a sustainable route to address these challenges. Herein, we report a moisture-induced energy harvesting strategy to realize efficient sorption-based atmospheric water harvesting (SAWH) and 24-hour thermoelectric power generation (TEPG) by synergistically utilizing moisture-induced sorption/desorption heats of SAWH, solar energy in the daytime and radiative cooling in the nighttime. Notably, the synergistic effects significantly improve all-day thermoelectric power density (~346%) and accelerate atmospheric water harvesting compared with conventional designs. We further demonstrate moisture-induced energy harvesting for a hybrid SAWH-TEPG device, exhibiting high water production of 750 g m−2, together with impressive thermoelectric power density up to 685 mW m−2 in the daytime and 21 mW m−2 in the nighttime. Our work provides a promising approach to realizing sustainable water production and power generation at anytime and anywhere.